Effects of GFF Bands on Normal and High Strength Concrete Cylinders - Jayaprakash, J.; Abdul Samad, Abdul Aziz; Mohamad, Noridah; Choong, K.K.; Megat Azmi, M.J.; Badorul, H.A.B. (International Journal of Integrated Engineering, 2010)
This paper exemplifies the effects of externally confined Glass Fibre Fabric (GFF) bands on normal and high strength concrete cylinders. Twelve normal and high strength concrete cylinders were cast and tested in the laboratory environment under axial compression to failure. The experimental results show that the degree of confinement of discrete GFF confined high strength concrete cylinders was significantly better than normal strength concrete cylinders with GFF bands, however the ductility of GFF confined high strength concrete cylinders was relatively less than GFF normal strength concrete. It was also found that the application of horizontally oriented GFF bands is the most effective confining pattern than spirally oriented GFF bands.